PERAN PEMERINTAH DALAM MENINGKATKAN KESEJAHTERAAN PETANI DI KABUPATEN GAYO LUES PROVINSI ACEH - Senja, Jusmaleara (PERSPEKTIF, 2014)
This study aims to analyze and determine the Government?s role of the GayoLues District whilw realizing The Farmers Society Movement Welfare Programme (GEMASIH) in order to improve the welfare of farmers and the obstacles encountered in the effort to improve the welfare of the farming community.The type of this research is descriptive. The results clarify that the government?s role in the development of the welfare GayoLues farmers are realized through the implementation of the tasks and work associated with the development of the agricultural sector in the district of Gayo been implemented. Nevertheless there are still some side action effectiveness and quality of human resources that need more intensive attention in the future